Pemberdayaan UMKM Lokal Melalui Pemanfaatan Pasar Malam Kadumekar Purwakarta - Jalaludin, Jalaludin; Ulpah, Dina Mariana; Yusuf, Nawaf; Apriyadi, Anton (STIE Syariah Indonesia Purwakarta, 2025)
Based on the results of observations, the PKM team found several unique phenomena related to the empowerment of local MSMEs through the use of the Kadumekar night market, one of which is that Kadumekar MSMEs still have difficulty in marketing the products produced, the Kadumekar Night Market is one of the initiatives that can be utilized to empower local MSMEs, the night market is not only a place for economic transactions, but also a means of social and cultural interaction that can strengthen the community, and the Kadumekar night market is a magnet for business actors from various regions. The purpose of this PKM is to socialize the empowerment of local MSMEs through the use of the night market, so as to increase the income of local MSME players. This PKM method uses observation, socialization and discussion, monitoring and evaluation. The conclusion of this PKM is that before the socialization of MSME empowerment through the use of the night market, the average value of respondents was 27.77 (very not understanding), while after the PKM activity the average value of respondents was 83.33 points of understanding criteria. In addition, this PKM MSME actors have understood the use of the night market to increase income, methods to attract night market customers so that the products and services offered are in great demand, have known the benefits of direct interaction with night market customers, have been able to optimize the potential of the night market, have known the promotion strategy at the night market, have known the strategy for choosing the right business location to attract customers and increase sales opportunities, and have known the importance of product branding from product labels to product packaging.